2017
DOI: 10.1039/c6ra28056k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of sodium thiosulfate pentahydrate/silica microencapsulated phase change material for thermal energy storage

Abstract: Microencapsulated phase change materials (MicroPCM) were successfully fabricated by encapsulation of sodium thiosulfate pentahydrate (SoTP) as core with silica shell using sol–gel method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Similar work has been done by Liu et al , on the encapsulation of sodium thiosulfate pentahydrate into microcapsules with silica shell. 170 The authors demonstrated successful encapsulation of inorganic PCM into silica shell by sol–gel method with high encapsulation rate (94.65 wt%). However, the stability of the capsules during the heat uptake/release cycles was not demonstrated.…”
Section: Encapsulation Of Inorganic Pcmsmentioning
confidence: 97%
“…Similar work has been done by Liu et al , on the encapsulation of sodium thiosulfate pentahydrate into microcapsules with silica shell. 170 The authors demonstrated successful encapsulation of inorganic PCM into silica shell by sol–gel method with high encapsulation rate (94.65 wt%). However, the stability of the capsules during the heat uptake/release cycles was not demonstrated.…”
Section: Encapsulation Of Inorganic Pcmsmentioning
confidence: 97%
“…One of the most promising materials used in order to store latent heat are the phase changing materials (PCMs) because they can store 5-14 times more energy than classical materials [9,10]. According to Soares et al [9], PCMs integrated in building envelope or building systems could determine the following benefits: Phase changing materials is a TES medium that draws the attention of many researchers over the last decade [11,12] and according to Navarro et al [6] these materials can improve the overall efficiency of systems using renewable energy sources by storing the surplus energy and using it during the periods when the source is not available (e.g. during night-time in case of solar radiation).…”
Section: Latent Heat Thermal Energy Storage (Lhtes)mentioning
confidence: 99%
“…Capsules offer a confined space with a higher heat transfer area, reduced reactivity with the outer environment, and controlled changes of volume during the phase transition . Diverse chemical (e.g., emulsion/miniemulsion polymerization, , phase separation, solvent evaporation, , in situ polymerization and solvent evaporation, , interfacial polymerization, or surface-thiol Michael addition polymerization), physicochemical (e.g., sol–gel and inorganic precipitation processes), , and mechanical (e.g., mechanical packaging with or without electroplating methods) techniques have been successfully used for the encapsulation of salts and hydrated salts . Sodium phosphate dodecahydrate, sodium sulfate decahydrate, magnesium nitrate hexahydrate, and mixtures of two different salts were commonly encapsulated within different polymer (e.g., PMMA , or poly­(ethyl-2-cyanoacrylate) , ), inorganic (e.g., silica), , or polymer–inorganic (e.g., polyurethane–silica) hybrid capsules.…”
Section: Introductionmentioning
confidence: 99%